Integrasi Ketaatan Dan Kesetiaan Hosea Sebagai Refleksi Iman Bagi Kepala Keluarga Kristen Masa Kini Berdasarkan Hosea 3:1-5 - Lestari Loi; Christovel Lubis; Grecetinovitria Merlina Butar-butar (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Obedience and loyalty are an inseparable integration in the life of a Christian. As a follower of Christ, these two personality traits are characteristics that must be possessed. This character was owned by a prophet named Hosea. The rise of infidelity and divorce, which is increasingly rampant at the moment, is attracting deep attention because Christian families are also falling into it. The head of the family plays a very important role in controlling and controlling the family. This research uses the method. In this article, the author uses the library study method, where this literature study is a study of ideas, concepts or theories originating from related literature sourced from books and journals that are recognized nationally and internationally using a hermenetic approach and phenomenology so that this method can help in analyzing and identifying scientific articles. This research examines how Hosea's obedience and loyalty are a reflection of faith for today's Christian family heads.